TEKNIK IMOBILISASI ADSORPSI DAN ENTRAPMENT FILM NATA DE COCO-BENEDICT UNTUK DETEKSI KADAR GULA DALAM URIN - Meyliana Wulandari (JURNAL ISTEK, 2011)
Person with Diabetes Mellitus (DM) usually have high level of sugar in his blood. He also has trouble on glucose transportation in his kidneys, so his urine has high glucose concentration. It was synthesized of chemical sensor based on Benedict to measure glucose level. Cellulose from nata de coco is used as supporting material for Benedict immobilization. The characteristics of sensor are determined through sensor leaching, linear range, limit of detection, reproducibility, and sensitivity by reflectance spectrophotometry. The parameter which needs to be optimal at adsorption method is Benedict concentration and the time of dipping. While at entrapment method optimation is rasio of cellulose mass: Benedict volume and Benedict concentration. The optimal result of maximum wavelength of Benedict cellulose sensor with both methods is 541.57 nm. Optimum condition of dipping time is 40 minutes. Rasio of cellulose: with Benedict volume optimum at 1: 3, with optimal concentration of Benedict is 0.2682 M at adsorption method and 0.4470 M at entrapment method. The amounts of leaching at entrapment method is smaller than amounts at adsorption method. Sensor characteristics with adsorption method are better than with entrapment method. The result of glucose level measurement at urine which uses adsorption method and entrapment sensor has small differences with level of glucose data which uses Nelson-Somogyi standard method. So, adsorption is method of Benedict cellulose sensor which is more accurate for determining glucose level in urine.